Comparison of postoperative quality of life of Limberg flap and Karydakis flap in pilonidal sinus operations - Destek, Sabahattin (Turk J Surg, 2020)
OBJECTIVES: Pilonidal sinus disease (PSD), most commonly seen in young men, is a chronic disease resulting from the pilosebaceous in the sacrococcygeal region. There is still no standardization in surgical treatment. In this study, the effectiveness, follow up outcomes and quality of life level were compared between Karydakis flap (KF) and Limberg flap (LF) operations. MATERIAL AND METHODS: Among the patients who had undergone PSD surgery in our clinic between 2015 and 2016, those who could be reached and who received KF (n= 53) and LF (n= 51) operations were included into the study. Clinical data of these patients were retrospectively evaluated. Postoperative satisfaction levels of the patients were determined with Cardiff wound healing survey questions and visual analog scale. RESULTS: Mean operational time was 54 (44-75) minutes in the LF group and 45 (35-60) minutes in the KF group, and it was statistically significant (p= 0.001). Mean time to return to work was 14.3 (9-28) days in the LF group and 17.6 (10-30) days in the CF group and was statistically significant (p= 0.001). The rates of complications and recurrence were lower in the LF group although the difference was not statistically significant between the groups (p> 0.05). Mean psychosocial assessment score was 70.3 (57.5-88.7) in the KF group and 73.4 (53.5-87.5) in the LF group and the difference was statistically significant (p= 0.001). CONCLUSION: LF was a more reliable and preferable method compared to KF because of earlier return-to-work, lower rate of recurrence at long term follow up, and higher psychosocial satisfaction.